2008
DOI: 10.1088/1741-2560/5/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Improved bladder emptying in urinary retention by electrical stimulation of pudendal afferents

Abstract: Urinary retention is the inability to empty the bladder completely, and may result from bladder hypocontractility, increases in outlet resistance, or both. Chronic urinary retention can lead to several urological complications and is often refractory to pharmacologic, behavioral, and surgical treatments. We sought to determine whether electrical stimulation of sensory fibers in the pudendal nerve could engage an augmenting reflex and thereby improve bladder emptying in an animal model of urinary retention. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…Chronic neuromodulation specifically involves central structures in micturition and continence control, whereas acute SNM predominantly modulates brain areas that are involved in sensorimotor learning [35]. Moreover, pudendal sensory feedback is crucial for bladder emptying [13,37]. Recent studies have indicated that acute ES of the pudendal nerve may immediately produce positive afferent feedback to the detrusor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic neuromodulation specifically involves central structures in micturition and continence control, whereas acute SNM predominantly modulates brain areas that are involved in sensorimotor learning [35]. Moreover, pudendal sensory feedback is crucial for bladder emptying [13,37]. Recent studies have indicated that acute ES of the pudendal nerve may immediately produce positive afferent feedback to the detrusor (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the opossums do not have cecotrophic habits as found in rabbits which distress procedures affect species nutritional balances. This could be a great advance over the use of rats and rabbits with known models problems [6,10,31].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the pathways of peripheral innervation is an important tool to study EUS function in preclinical studies (Cruz & Downie 2005;Jiang et al 2009aJiang et al , 2009bKamo & Hashimoto 2007;Kamo et al 2009;Kamo et al 2003;Kerns et al 2000;Lee et al 2003;Peng et al 2008aPeng et al , 2008b). Animal models have been used to estimate the damage to nerves during simulated childbirth and to test pharmacological and neuromodulation strategies to promote neuroregeneration and recovery of EUS function Cannon et al 2002;Jiang et al 2009aJiang et al , 2009bPeng et al 2008a;Streng et al 2001;Thor 2003;Thor et al 1989;Thor et al 2007;Vera & Nadelhaft 2001).…”
Section: Innervation Of the Eusmentioning
confidence: 99%
“…Animal models have been used to estimate the damage to nerves during simulated childbirth and to test pharmacological and neuromodulation strategies to promote neuroregeneration and recovery of EUS function Cannon et al 2002;Jiang et al 2009aJiang et al , 2009bPeng et al 2008a;Streng et al 2001;Thor 2003;Thor et al 1989;Thor et al 2007;Vera & Nadelhaft 2001). EMG EUS activity, or contraction, is usually measured along with bladder pressure, urethral pressure, leak point pressure and/or voiding frequency before and after a lesion to or stimulation of one or more of the nerves that innervate the EUS (Cruz & Downie 2005;Jiang et al 2009b;Peng et al 2006;Peng et al 2008aPeng et al , 2008b. However, it is difficult to compare results because some studies do not describe the site of the nerve lesion and the dissection procedures to access the nerves differ between studies (Cruz & Downie 2005;Damaser et al 2007;Furuta et al 2008;Kamo et al 2003;Kim et al 2009;Peng et al 2006;Wai et al 2004).…”
Section: Innervation Of the Eusmentioning
confidence: 99%